Cost performance improvement in the Green Transit Oriented Development (TOD) area based on Blockchain-Building Information Modelling (BIM) - Husin, Albert Eddy; Damayanti, Elysa; Rohman, Muhammad Nur; Ator, Wyllem (Universitas Ibn Khaldun Bogor, 2025)
The emission and mitigation of greenhouse gases transforms the status of urban environ ments. However, a policy accounting for all the aspects associated with transport is lacking. Prob lems related to transport include a greater reliance on cars, increased congestion, and environmental impacts. The absence of an efficient public transport system is a notable cause of the prompt escala tion of diverse problems, for example, increases in the number of personal automobiles causes con gestion on the road, resulting in air pollution, ubiquitous greenhouse effects and noise pollution, which ultimately affect human health. Over the past two decades, a growing number of communities have pursued light rail transit (LRT) and Transit-Oriented Developments (TODs) as part of an integrated transportation and land use strategy to revitalize and/or regenerate the built environment of worldwide cities. Green TOD focuses on combining TOD with green neighborhood to generate larger ecological and environmental benefits. In their research, Cervero and Sullivan suggested that the combination should be realized in the following aspects: (1) higher densities, (2) mixed land use, (3)reduced. The integration of Blockchain with BIM for data provenance uses a distributed network for storing provenance data over a decentralized and fault-tolerant ledger With the results of this research, there is expected to be shared awareness and concern about implementing green neighborhood and green space as an initiative to present a more energy-efficient transit oriented, save operating costs, and provide comfort to customers.